A FRAMEWORK FOR EFFECTIVE E-COLLABORi\ TION AND DiDACTICS ENHANCEMENT - YUSSIFF, ALIMATU-SAADIA (2016)
This thesis developed and validated a framework for effective e-collaboration and didactics enhancement. Three major problems identified at the onset of this research are; lack of comprehensive framework to serve as a commonly accepted framework for e-collaboration design and usage; gaps between constructivist online instructional design, teaching approaches and actual practices; and lack of social media use for collaboration. In an attempt to bridge these gaps, this research proposed four main objectives: To identify prior learning theories, frameworks, models and related works one-collaboration in order to identify relevant constructs, key variables and didactics for online collaborative leaming and teaching; to develop a framework for effective ecollaboration and didactics enhancement for higher educational institution; to develop an e-collaboration system entitled Teach, Learn, and Research e-Collaboration System (TELERECS); and finally, to validate the framework.